Characterization of pulmonary function in Duchenne Muscular Dystrophy. Issue 5 (9th March 2015) - Mayer, O.H.; Finkel, R.S.; Rummey, C.; Benton, M.J.; Glanzman, A.M.; Flickinger, J.; Lindström, B.‐M.; Meier, T.
Summary Decline in pulmonary function in Duchenne Muscular Dystrophy (DMD) contributes to significant morbidity and reduced longevity. Spirometry is a widely used and fairly easily performed technique to assess lung function, and in particular lung volume; however, the acceptability criteria from the American Thoracic Society (ATS) may be overly restrictive and inappropriate for patients with neuromuscular disease. We examined prospective spirometry data (Forced Vital Capacity [FVC] and peak expiratory flow [PEF]) from 60 DMD patients enrolled in a natural history cohort study (median age 10.3 years, range 5–24 years). Expiratory flow‐volume curves were examined by a pulmonologist and the data were evaluated for acceptability using ATS criteria modified based on the capabilities of patients with neuromuscular disease. Data were then analyzed for change with age, ambulation status, and glucocorticoid use. At least one acceptable study was obtained in 44 subjects (73%), and 81 of the 131 studies (62%) were acceptable. The FVC and PEF showed similar relative changes in absolute values with increasing age, i.e., an increase through 10 years, relative stabilization from 10–18 years, and then a decrease at an older age. The percent predicted, FVC and PEF showed a near linear decline of approximately 5% points/year from ages 5 to 24. Surprisingly, no difference was observed in FVC or PEF by ambulation or steroid treatment. Acceptable spirometry can be performed on DMD patients over a broad range of ages. Using modified ATS criteria, curated spirometry data, excluding technically unacceptable data, may provide a more reliable means of determining change in lung function over time. Pediatr Pulmonol. 2015; 50:487–494. © 2015 Wiley Periodicals, Inc.